The impact of virtual rheumatology care on patient outcomes and hospital admissions: an ambispective study - Ummugulsum Gazel; Tommy Han; Seyyid Bilal Acikgoz; Tara Swami; Ricardo Sabido-Sauri; Hart Goldhar; Nataliya Milman; Nancy Maltez; Catherine Ivory; Susan Humphrey-Murto; Sibel Aydin (BMC Rheumatology)
Abstract Introduction The impact of virtual care on clinical outcomes, healthcare resources and long-term patient satisfaction will help to inform healthcare providers. We aimed to evaluate the impact of virtual rheumatology care on patients’ clinical outcomes and healthcare utilization. Methods Patients who had at least a phone-visit during the early-pandemic and enrolled in a previous survey were invited to attend this study. Through patient surveys and review of medical charts, patients’ clinical outcomes were collected, face-to-face visits in the pre-COVID-19 era (Jan 2019, 2020) and virtual care visits (VCV) in the pandemic period (Mar 2020-June 2021). Results Within 226 patients, the total number of rheumatology (median (IQR): 2 (2–3) vs. 3 [2, 3, 4], p < 0.001), emergency visits (19% vs. 29.3%, p:0.006) and hospital admissions (12.9% vs. 20.8%, p:0.015) due to any cause were increased during the pandemic, whereas there was no increased ER visit or admissions due to their rheumatological disease. Around 1/3 of patients reported being on more pain medication during the COVID-19-period. Failed VCV, requiring an additional in-person-visit within 60 days, was observed in 23 (8.3%) patients and 25 (3.1%) of 800 VCV. Close to 50% of the patients with failed-VCV were treated with additional steroid therapies during the pandemic. Discussion Our results support ongoing VCV with no increased healthcare utilization and a low rate of failed visits. These findings suggest that virtual care is here to stay for some patients and in some circumstances, and it is important to establish algorithms for implementing it to healthcare system. Our results provide evidence to inform insurers’ decision-making regarding virtual care.